First in vitro lipid peroxidation and in vivo anti-inflammatory activity of the Omani frankincense of Boswellia sacra Flueck. - Ahmed Al-Harrasi; Ahmed Al-Rawahi; Javid Hussain; Liaqat Ali; Hidayat Hussain; Najeeb Ur Rehman; Ghulam Abbas; Mehjabeen; Rashid Al-Harrasi (International Journal of Phytomedicine, 2013)
The use of frankincense for the medicinal and religious purposes dates back to the early Egyptians, the Greeks, and the Chinese and today, it is commonly used as an anti-inflammatory, antiseptic, anti-tumor, sedative and diuretic agent. To prove the scientific basis of the anti-inflammatory properties and the in vitro lipid peroxidation of the Omani Frakincense on pharmacological grounds, the present study was conducted. The crude extract, the essential oils and various sub-fractions of the crude methanolic extract (300 mg/kg of the body weight of the animals) obtained from the resin of Boswellia sacra Flueck. were evaluated for their in vivo anti-inflammatory activities using carrageenan-induced hind paw edema in rats and in vitro lipid peroxidation by using the thiobarbituric acid reactive substance (TBARS) assay. The tremendous folk use of frankincense as an anti-inflammatory agent was rationalized by our present study of the in vitro TBARS assay and the in vivo anti-inflammatory activities. To the best of our knowledge, this is the first report of the anti-inflammatory activity studies which has been conducted thoroughly on the essential oils, the crude extract and the various sub-fractions obtained by using various polarity organic solvents on the resin of the plant Boswellia sacra Flueck.